Factors Influencing Use–diversity of Urban Parks: A Cross-cultural Study Between Chengdu (China) and Perth (Australia). (September 2022) - Swapan, Mohammad Shahidul Hasan; Iftekhar, Md. Sayed; Li, Xiyuan
Urban parks are an essential component of city infrastructure providing multiple ecosystem services. While there are many studies exploring the usage of urban parks within a country, cross-country comparisons are rare. Comparative studies of use–diversity of urban parks between developing and developed countries are almost absent. To address this research gap, we have compared use–diversity of two major urban parks in China (Dufu Cottage in Chengdu—DC) and in Australia (Kings Park in Perth—KP). Using a post-occupancy survey questionnaire, we addressed two key questions: (a) is there any difference in use–diversity between these urban parks? And (b) which demographic and socio-economic factors influence use pattern of urban parks the most? We observed that, in general, use frequency is lower in DC when compared to KP. In both parks, the opportunity of physical activity is the most important motive for visitation. Most of the usage is concentrated during the weekends in DC; KP was used more consistently throughout the week. Various socio-demographic factors, such as gender, age, income level and frequency of visits, have some influence on frequency and diversity of usage. The impact of socio-demographic factors on the extent of use highlights the importance of understanding users' profiles to adopt more targeted measures to address local demands. The study identified some common patterns and differences in use–diversity between the two parks, underscoring the potential for managers of these parks in both countries, for mutual learning and adopting best management practices.